The mechanisms of Brucea javanica in the treatment of oral squamous cell carcinoma: a network pharmacology, molecular docking, and experimental study - MingKang Li; Juan Zhan; YiHan Lai; YuJie Ma; HongCheng Wei; Lin Jiang; JuanJuan Zha; YiSen Shao; Wei Wang (European Journal of Medical Research)
Abstract Objective To elucidate the potential targets and mechanisms of Brucea javanica in the treatment of oral squamous cell carcinoma (OSCC) through network pharmacology and molecular docking, supported by clinical data and in vitro experiments. Methods Potential targets of Brucea javanica and OSCC-related disease targets were identified via the TCMSP, GeneCards, and OMIM databases. A Venn diagram was employed to obtain the intersection targets, which were considered as the potential targets for Brucea javanica in OSCC treatment. The protein–protein interaction (PPI) network was constructed using the STRING database and Cytoscape 3.7.2 to identify core targets. Gene ontology (GO) function enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of the intersection targets were conducted using the Metascape database. Molecular docking between the main components of Brucea javanica and core targets was performed using AutoDockTools software. The expression of core targets in clinical samples was analyzed via the GEO database. Finally, the effects of Brucea javanica oil (BJO) on OSCC proliferation, invasion, and migration, as well as the expression of the EGFR/PI3K/AKT signaling pathway, were verified in vitro. Results A total of 60 potential targets of Brucea javanica against OSCC were identified, with β-sitosterol and luteolin selected as the primary active components. The five targets with the highest connectivity, AKT1, CASP3, PTGS2, TP53, and EGFR, were identified as core targets. KEGG pathway analysis indicated that the anti-OSCC effects of Brucea javanica are primarily mediated through the PI3K-AKT signaling pathway, JAK-STAT signaling pathway, etc. Molecular docking studies demonstrated strong binding affinities between the main components of Brucea javanica and its core targets. Analysis of clinical samples revealed elevated expression levels of core targets in OSCC samples compared to normal samples. The CCK-8 assay and colony formation assay indicated that BJO effectively inhibited OSCC cell proliferation. The scratch test and Transwell test showed that BJO could inhibit the invasion and migration of oral squamous cell carcinoma. In addition, Western blot and RT-qPCR showed that BJO could down-regulate the expression of EGFR/PI3K/AKT signaling pathway-related proteins and mRNA. Conclusion Brucea javanica exhibits multi-target and multi-pathway characteristics in the treatment of oral squamous cell carcinoma, potentially exerting its anti-cancer effects by inhibiting the EGFR/PI3K/AKT signaling pathway.